2015
DOI: 10.1074/jbc.m115.647461
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Evolution of the Archaeal Lipid Synthesis Enzyme sn-Glycerol-1-phosphate Dehydrogenase

Abstract: Background: Archaea synthesize glycerol-based membrane lipids of unique stereochemistry, utilizing distinct enzymology. Results: The structure of sn-glycerol-1-phosphate dehydrogenase (G1PDH), the first step in archaeal lipid synthesis, was determined. Conclusion: G1PDH is a member of the iron-dependent alcohol dehydrogenase and dehydroquinate synthase superfamily. Significance: The data contribute to our understanding of the origins of cellular lipids at the divergence of the Archaea and Bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 70 publications
(89 reference statements)
5
22
0
Order By: Relevance
“…The reaction rate with NADPH ( VmaxNADPH = 0.007 ± 0.01 μmol/sec/mg) was only 2.4% of that with NADH ( VmaxNADH = 0.30 ± 0.027 μmol/sec/mg), indicating that NADH is favored as the natural cofactor. This finding is a striking feature of P. calidifontis G1PDH, because the four previously characterized G1PDHs show a significant preference for NADPH when V max / K m values are compared, indicating that the P. calidifontis enzyme is a novel type of G1PDH. The K m value for NADH and NADPH was determined to be 0.077 ± 0.01 m M and 0.031 ± 0.011 m M respectively, when 4 m M DHAP was used.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…The reaction rate with NADPH ( VmaxNADPH = 0.007 ± 0.01 μmol/sec/mg) was only 2.4% of that with NADH ( VmaxNADH = 0.30 ± 0.027 μmol/sec/mg), indicating that NADH is favored as the natural cofactor. This finding is a striking feature of P. calidifontis G1PDH, because the four previously characterized G1PDHs show a significant preference for NADPH when V max / K m values are compared, indicating that the P. calidifontis enzyme is a novel type of G1PDH. The K m value for NADH and NADPH was determined to be 0.077 ± 0.01 m M and 0.031 ± 0.011 m M respectively, when 4 m M DHAP was used.…”
Section: Resultsmentioning
confidence: 76%
“…Previous studies on M. thermoautotrophicus G1PDH have suggested that this enzyme is a homooctamer in solution, whereas A. pernix G1PDH forms a dimeric structure . On the other hand, M. jannaschii G1PDH was proposed to have a monomeric structure, although the enzyme forms a dimeric structure in a crystal form. In this regard, P. calidifontis G1PDH differs substantially from the three other G1PDHs previously described.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations